Uso de plaguicidas químicos en el cultivo de cacao (Theobroma cacao) y su influencia con el medio ambiente en el Ecuador. - Morante Solís, Elvis Andrés (2022)
This research work verified the environmental impact caused by the use of pesticides in the cultivation of cocoa (Theobroma cacao) in Ecuador; an investigative methodology was used in which a thorough collection of bibliographic information was carried out in a truthful manner, whose data obtained through books, theses, scientific articles, blogs or web pages, manuals and journals. The information was processed through the technique of analysis, synthesis and summary, verifying that the misuse or manipulation of pesticides in the cultivation of cocoa causes an environmental impact; where biodiversity is affected causing climatic changes that will influence the crop, therefore, it is also harmful to humans, since it has been detected that exposure affects the digestive system and causes infections and kidney inflammations. The research analyzed led to the conclusion that the growing dependence on and abuse of pesticides with persistent chemical structures alters the ecology and ecological balance, preventing terrestrial ecosystems from self-purifying and self-regulating. Considering the above, it is recommended to promote the use of biopesticides on farms and to encourage producers to implement integrated plant protection.